The Effect of Pedestrian Countdown Signals on Pedestrian Walking Speed - Campbell, Alexandra (2015)
This research investigates the effect of pedestrian countdown signals (PCS devices) on crossing walking speed of pedestrians at urban signalized intersections. The research considers two age groups: (1) younger pedestrians (ages 20 to 64); and (2) older pedestrians (ages 65 and older).